Pendampingan Masyarakat Sekolah dalam Meningkatkan Kesadaran Menjaga Kebersihan Lingkungan - Idami, Zahratul; Rifa'ah, Sirriyatur; Muntiza, Rizka; Navisa A, Alya; Nurisa, Vina; Ramadani, Fitria (Catimore: Jurnal Pengabdian Kepada Masyarakat, 2024)
Healthy and clean environment is something that must be initiated for the survival of future generations so that it is not threatened by the consequences of irresponsible human behaviour. This community service is inspired by the lack of students’ awareness in maintaining environmental cleanliness and the lack of cleaning facilities at MTs MIM Langsa. The procedure of this assisting activity is carried out through 3 stages, namely: planning, implementing, and reflecting, which begins with field observation to the target school. This potential-based community service activity is in the form of counseling/socialization and mentoring on school environmental hygiene. Socialization activities targeting OSIM administrators of MTs MIM Langsa as role models are expected to motivate other students to always maintain school cleanliness. Meanwhile, other activities include painting garbage cans and providing posters with the theme of environmental cleanliness. The provision of cleaning facilities in the form of garbage cans in several places in the school environment has received positive responses and support from the school community, one of which is showed by students who responsibly do class pickets and do not litter.